COMBINED WANPRESTASI LAWSUIT AND AGAINST THE LAW REVIEW OF THE JUSTICE SYSTEM IN INDONESIA - Annga Alfiyan (JIL : Journal of Indonesian Law, 2022)
Civil lawsuits are not only lawsuits for default, but are also dominated by lawsuits against the law. The difference between a breach of contract and against the law is that the claim for default is to place the loss in a position where the compensation given is the expected loss, while the lawsuit for the unlawful act of the plaintiff is in a position before the unlawful act so that the compensation given is a real loss. The results of the study show that civil lawsuits in the field are dominated by lawsuits against the law, besides of course the lawsuit for breach of contract. To file a lawsuit, the act against the law must be ascertained as stipulated in Article 1365 of the Civil Code, while to file a lawsuit for default, it must comply with the provisions of Article 1243 of the Civil Code. Based on this, the author examines it as a court that is simple, fast, and cheap in accordance with the law No. 48 of 2009 concerning Judicial Power with the concept of Merger of Lawsuits.